NT-proBNP levels and mortality in a genera population-based cohort from Turkey: a long-term follow-up study - MUTLU, BÜLENT (FUTURE MEDICINE LTD, 2018)
Aim: We investigated the relationship between NT-ProBNP and mortality in a general population-based cohort. Methods & Results: A total of 2021 out of 4650 participants from previously published HAPPY study were included. Mean follow-up was 84.5 +/- 10.4 months. After adjusting for risk factors, high levels of LogNT-proBNP predicted all-cause death (HR: 3.23; 95% CI: 2.20-4.75; p < 0.001) and cardiovascular death (HR: 3.85; 95% CI: 2.37-6.26; p < 0.001). Regression analysis revealed that LogNT-proBNP was an independent predictor of all-cause death (HR: 2.85; 95% CI: 1.91-4.24; p < 0.001) and cardiovascular death (HR: 3.02; 95% CI: 1.84-4.95; p < 0.001). Conclusion: Our study showed that in long term follow-up, NT-proBNP is associated with increased all-cause and cardiovascular mortality
Keywords: all-cause mortality; cardiovascular epidemiology; cardiovascular mortality; general population; NT-proBNP; BRAIN NATRIURETIC PEPTIDE; CARDIOVASCULAR EVENTS; HEART-FAILURE; BIOMARKERS; RISK; PREDICTORS; DEATH; MEN